Performing for the camera - Baker, Simon, 1972-; Moran, Fiontán (Tate Publishing, 2016)
Performing for the camera' examines how the photograph has both documented and developed our understanding of performance since the invention of the photographic medium. It engages with both the serious business of art and performance and the humour and improvisation of posing for the camera. Featuring many of the most compelling and experimental photographers in history, it explores the works by artists such as Yves Klein, Yayoi Kusama, Nadar, Merce Cunningham, Charles Ray, Boris Mikhailov, Samuel Fosso, Cindy Sherman, Keith Arnatt and Masahisa Fukase. Edited by curator Simon Baker, this book provides fresh insight into the inter-relationship between performance and photography. With over 300 illustrations, this is the definitive publication on two of the most popular and intriguing art forms of our time. Exhibition: Tate Modern, London, UK (18.02-12.06.2016).